A review of diagnostic criteria, traits and types of borderline personality with an attempt to order them - Brud, Piotr (Studia Psychologica: Theoria et praxis, 2021)
Borderline personality disorder is one of the most common disorders and at the same time quite problematic to diagnose, as successive editions of the DSM and ICD have pointed out. The heterogeneity of borderline personality has long been demonstrated. It has generally been shown using two complementary approaches: (1) variable-centered, where factors were extracted, and (2) person-centered, where types were identified as configurations of variables. This paper presents a review of the literature on borderline personality variation in both approaches. Thirty-seven borderline models were identified, including 12 that used a variable-centered approach and 25 that used a person-centered approach. In these models, single units of meaning were distinguished, which the authors used to describe borderline personality. A total of 59 such units were distinguished, which were then combined into 11 meaning-consistent groups.